The Smithsonian?Enola Gay Controversy: Including Wisconsin Perspectives on the Exhibit and the Atomic Bombings - Aukema, Justin (My University, 2008)
This paper examines the Smithsonian?Enola Gay controversy, an event which took place between 1993 and 1995. The controversy had broad implications for the field of history and the arena of American public consciousness. In an attempt to portray the end of World War II, the atomic bombings of Hiroshima and Nagasaki, and the nuclear arms race, the National Air and Space Museum ran into great opposition from various military groups and certain members of Congress. Each of these groups supported their own agendas; however, they all centered their arguments on what they say as a lack of balance in the Smithsonian exhibit. Scholars have noted, however, that the real issue at stake was a difference in the way America?s role in history was viewed. The Smithsonian wished to portray an accurate picture, even at the cost of exposing America?s not so innocent past. The events sparked conversation about the atomic bombings and around the United States people discussed the events. In Wisconsin, there was lively debate and discussion.
Keywords: National Air and Space Museum--Exhibitions--Political aspects; Hiroshima-shi (Japan)--History--Bombardment, 1945; Enola Gay (Bomber)--Exhibitions--Political aspects; Atomic bomb--Moral and ethical aspects